Implementation And Analysis Of Hot Standby Router Protocol (HSRP) For Gateway Redundancy In Networks At XYZ Tbk - Taufik Rahman; Kautsar Imam Hidayat (Jurusan Teknik Informatika Fakultas Teknik Universitas Trunojoyo Madura, 2025)
This study examines the implementation of the Hot Standby Router Protocol (HSRP) as a gateway redundancy mechanism within the Cisco-based network of Perusahaan XYZ Tbk to mitigate the risk of a single point of failure. The integration of HSRP with EIGRP, DHCP, VLAN, and ACL is applied to enhance routing efficiency, automate IP addressing, and strengthen overall network security. The research methodology includes observation, interviews, literature review, and network simulation using PnetLab. Initial testing on the existing network reveals connection failures when the primary gateway becomes unavailable due to the absence of a backup path. In contrast, testing on the proposed network shows that the failover mechanism successfully shifts traffic from the active router to the standby router without generating a Request Time Out (RTO), although a brief transition delay of up to 6.443 ms occurs. These findings indicate that HSRP effectively maintains network availability and service continuity. Furthermore, the application of EIGRP improves route exchange, DHCP simplifies IP management, and VLAN along with ACL enhances traffic segmentation and network security. Overall, the proposed design provides higher reliability and performance than the existing network.Keywords: HSRP, Failover, Redundancy, EIGRP, Network